Silicon-mediated stoichiometric controls on phytoplankton community shifts in the Yangtze and Yellow Rivers - Li Yingxiao; Chi Yuning; Zhong Xiaosong; Liu Xiaotian; Lv Zongqing; Wu Wentao; Ran Xiangbin (Journal of Hydrology, 2026)

Construction of a heterojunction based on polyphthalocyanine and defective ZnIn2S4 for enhanced CO₂ photoreduction performance - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Journal of Environmental Chemical Engineering, 2026)

Quantitative attribution of seasonal runoff variations in the Yellow River Basin under unsteady conditions using a modified Budyko framework - Junjie Wang; Yuning Chi; Shaoxiong Zhang; Bing Shi; Liting Zhang; Chenjun Du; Xin Li; Baoqi Li; Liqin Yang; Lei Huang; Dian Yuan; Kaiyang Qiu; et al. (Journal of Hydrology, 2026)

In situ preparation of heterometallic polyphthalocyanine/ZnIn2S4 heterojunction for efficient photocatalytic CO2 reduction - Yuxuan Liu; Yuning Liang; Weimeng Chi; Shuohui Li; Yanhua Gao; Ying Chen (Environmental Research, 2026)

Divergent hydrological responses of multi-depth soil moisture variability to multiple factors on the Loess Plateau, China - Junjie Wang; Shaoxiong Zhang; Yuning Chi; Bing Shi; Xin Li; Baoqi Li; Panxing He (Journal of Hydrology, 2026)

Preparation of superhydrophilic functionalized nZVI-MOF-74(Co)-PDA@PVDF composite membranes for enhanced Cr(VI) removal - Mingchun Bi; Yuning Liang; Weimeng Chi; Yuchao Cui; Yuxuan Liu; Juan Ren; Ying Chen (Environmental Research, 2025)

Enhanced removal of Cr(VI) from aqueous solutions using a zero-valent nickel/iron-PDA@PVDF membrane prepared via a simple blending method - Mingchun Bi; Yuning Liang; Weimeng Chi; Hongya Liu; Ying Chen (Chemical Engineering Journal, 2024)

Centrifuge model tests and numerical simulation on ground-borne vibration propagating and vibration reduction scheme for tunnel inner structure - Zhenghao Liu; Xianfeng Ma; Junyu Chi; Yuning Chen; Chen Wang (Tunnelling and Underground Space Technology, 2024)

Designing and fabricating a neoteric immobilized Z-scheme V2O5/FeVO4/430-stainless steel foil photocatalyst composite film for tetracycline degradation with synchronous hydrogen production - Yuning Tu; Ying Liu; Shengwei Chi; Ying Tian; Jiaqi Dang; Taiyu Jin; Dawei Fang; Jun Wang (Journal of Environmental Chemical Engineering, 2024)

Improving Water Quality in a Sea Bay by Connecting Rivers on Both Sides of a Harbor - Yuning Chi; Wenming Zhang; Yanling Liu; Xiaoyu Zhang; Wanqing Chi; Bing Shi (Journal of Marine Science and Engineering, 2024)
Improving water quality is imperative for many sea bays, including Laizhou Bay, China, to achieve sustainable marine development. In 2010, two 17.3 km long sand-retaining embankments were built in southwestern Laizhou Bay, which weakened the nearshore hydrodynamics and seriously impacted the water quality. To mitigate this issue, this study proposes connecting the two rivers on both sides of the embankments to improve the hydrodynamics and thus water exchange in the sea bay. The effectiveness was examined with a numerical model using Mike 21, which was validated for both tidal current velocity and direction at six monitoring locations in the sea bay. The results show that over 53% of the core research area displays an increase (0.0–0.4 m/s) in tidal current speed after the connection, primarily in and around the Haihengwei Fishing Port. Meanwhile, the Eulerian residual currents in the Haihengwei Fishing Port, Mi River estuary and Bailang River estuary become substantially larger (with a maximum increase of 0.16 m/s). In addition, the net transport distance of particles released near the connection increases by up to 39.89 km in one month. Overall, this case study demonstrates that connecting rivers next to a harbor can effectively improve hydrodynamics and thus improve water quality in the bay.